Eclipse modeling framework : a developer's guide / Frank Budinsky. - Budinsky, Frank
Part 1. EMF Overview Chapter 1. Eclipse Chapter 2. Introducing EMF Chapter 3. Model Editing with EMF.Edit Chapter 4. Using EMF—A Simple Overview Part II. Defining EMF Models Chapter 5. Ecore Modeling Concepts Chapter 6. Java Source Code Chapter 7. XML Schema Chapter 8. UML Part III. Using the EMF Generator Chapter 9. EMF Generator Patterns Chapter 10. EMF. Edit Generator Patterns Chapter 11. Running the Generators Chapter 12. Example—Implementing a Model and Editor Part IV. Programming with EMF Chapter 13. EMF Client Programming Chapter 14. EMF.Edit Programming Part V. EMF API Chapter 15. The org.eclipse.emf.common Plug-In Chapter 16. The org.eclipse.emf.common.ui Plug-In Chapter 17. The org.eclipse.emf.ecore Plug-In Chapter 18. The org.eclipse.emf.ecore.xmi Plug-In Part VI. EMF.Edit API Chapter 19. The org.eclipse.emf.edit Plug-In Chapter 20. The org.eclipse.emf.edit.ui Plug-In Appendix A. UML Notation Appendix B. Summary of Example Models.